2015
DOI: 10.21608/bvmj.2015.31866
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological assessment of Street Vended Meat Products sandwiches in kalyobia Governorate

Abstract: Contamination of ready-to-eat foods sold by street vendors rendering them unacceptable for human consumption and become a global health problem. This study aimed to examine the quality and safety of street vended meat products in kalyobia governorate. Eighty samples of meat products including 20 samples each of beef burger, kofta, sausages and hawawshi were randomly collected from the streetvendors in kalyobia governorate to evaluate their bacteriological quality. The results revealed that the mean values of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 8 publications
5
17
0
Order By: Relevance
“…It is evident from the results recorded in (Table 1) that the APC/g of the examined samples of cooked chicken and meat meals ranged from 2.1×10 3 to 1.7×10 4 with an average of 6.03×10 3 ± 1.45×10 3 /(cfu/g) for meat, 4.6×10 3 to 2.9×10 4 with an average 9.91×10 3 ± 2.18×10 3 / (cfu/g) for meat kofta, , 3.5×10 3 to 3.9×10 4 with an average 8.58×10 3 ± 1.65×10 3 / (cfu/g) for chicken and 6.0×10 3 to 7.7×10 4 with an average 2.03×10 4 ± 0.43×10 4 (cfu/g) for chicken kofta. The current results nearly similar to the results recorded by Sobieh (2014) found that the mean value of RTE kofta was 1.83×10 4 cfu/gm, while higher results was recorded by [14] who found that the mean value of APC of RTE kofta was 8.51×10 5 cfu/g, also higher results was recorded by [14] found that the mean APC of RTE chicken meals was 1.9×10 4 cfu/g and in RTE meat meals was1.2×10 4 cfu/g.high incidence of APC , may indicate that the cooking process was inadequate, or post cooking contamination had occurred, or the length of time and temperature control in storage or display facilities was inadequate to prevent bacterial contamination ,or that a combination of these factors was involved [15]. Results given in Table 2 revealed that the Acceptability of the examined samples of cooked meat and chicken meals based on their APC was (86.67% ) of meat samples were accepted samples but (13.33% ) of meat samples were unaccepted ,(73.33%) of beef kofta samples were accepted but( 26.67% )of beef kofta samples were unaccepted,(80%) of chicken samples were accepted but( 20%) of chicken samples were unaccepted and (60%) of chicken kofta were accepted but (40 % )of chicken kofta were unaccepted.…”
Section: Discussionsupporting
confidence: 91%
“…It is evident from the results recorded in (Table 1) that the APC/g of the examined samples of cooked chicken and meat meals ranged from 2.1×10 3 to 1.7×10 4 with an average of 6.03×10 3 ± 1.45×10 3 /(cfu/g) for meat, 4.6×10 3 to 2.9×10 4 with an average 9.91×10 3 ± 2.18×10 3 / (cfu/g) for meat kofta, , 3.5×10 3 to 3.9×10 4 with an average 8.58×10 3 ± 1.65×10 3 / (cfu/g) for chicken and 6.0×10 3 to 7.7×10 4 with an average 2.03×10 4 ± 0.43×10 4 (cfu/g) for chicken kofta. The current results nearly similar to the results recorded by Sobieh (2014) found that the mean value of RTE kofta was 1.83×10 4 cfu/gm, while higher results was recorded by [14] who found that the mean value of APC of RTE kofta was 8.51×10 5 cfu/g, also higher results was recorded by [14] found that the mean APC of RTE chicken meals was 1.9×10 4 cfu/g and in RTE meat meals was1.2×10 4 cfu/g.high incidence of APC , may indicate that the cooking process was inadequate, or post cooking contamination had occurred, or the length of time and temperature control in storage or display facilities was inadequate to prevent bacterial contamination ,or that a combination of these factors was involved [15]. Results given in Table 2 revealed that the Acceptability of the examined samples of cooked meat and chicken meals based on their APC was (86.67% ) of meat samples were accepted samples but (13.33% ) of meat samples were unaccepted ,(73.33%) of beef kofta samples were accepted but( 26.67% )of beef kofta samples were unaccepted,(80%) of chicken samples were accepted but( 20%) of chicken samples were unaccepted and (60%) of chicken kofta were accepted but (40 % )of chicken kofta were unaccepted.…”
Section: Discussionsupporting
confidence: 91%
“…In Ethiopia, food handler has been reported to suffer from diseases like diarrhoea, cholera, typhoid fever (Tesfaye, 2018). Studies showed that pathogens were frequently isolated in contaminated street food (Shaltot et al, 2015;Amare et al, 2019). Thus, foods handlers may lead to cross-contamination of food with bacteria when they suffer from specifics diseases.…”
Section: Knowledge Attitude and Practicesmentioning
confidence: 99%
“…The incidence and count results of total staphylococci in examined samples as mentioned in table (1) revealed that staphylococci were detected in 67.5% of all examined samples, represented by 73.3, 63.3, 50.0, and 83.3% with mean values 3.42x10 3 , 2.81x10 3 , 1.53x10 3 , and 0.20x10 3 CFU\g for kofta, burger, shawerma, and luncheon, respectively, which were in somewhat agreement with those reported by Rawash (2015) who recorded that mean values of total staphylococcal count in examined kofta and burger samples were 2.31×10 3 and1.57×10 3 CFU\g, respectively; Abd Allah-Mona (2016) who recorded that the mean value of total staphyloccal count in examined shawerma and kofta samples were 3.9x10 3 , 6.4x10 3 CFU\g, and Elshebacy (2017) who recorded that the mean value of total staphylococcal count in luncheon samples was 2.04x10 3 CFU\g; while they were different with those recorded by Abd Allah-Enas (2011) who found the mean value of total staphylococcal count in examined kofta sample was 9.14x10 2 CFU\g; Khater et al (2013) who recorded the mean value of total staphylococcal count in kofta samples 1.5x10 4 CFU\g; Youness (2018) (2.07x10 2 CFU\g for luncheon samples), and Bahbah (2019) (1.87x10 2 CFU\g for burger samples). In addition, the incidence and\or counts of S. aureus in examined as mentioned in table (2)revealed detection of S. aureus in 50.8% of all examined samples, where kofta was also the most contaminated samples with S. aureus followed by burger, shawerma, and luncheon with mean values 5.2x10, 3.2x10, 2.6x10 and 1.9x10 CFU\g, with incidences of 56.6, 43.3, 36.6, and 66.6%, respectively, which were somewhat agreed with those reported by Rawash (2015), Laban (2018) who recorded that the incidence of S. aureus in their examined RTE kofta, burger, shawerma, and luncheon was 60, 46.6, 40, and 60%, respectively; while they were different with that recorded by Ali and Abd-Elaziz (2011) who recorded that the average of S. aureus count in examined kofta, and shawerma samples were 7.2x10 4 and 8.98x10 3 CFU\g, respectively; Shaltout et al (2015), who recorded that the average of S. aureus count in examined burger samples was 7.54x10 2 CFU\g, respectively and Morshdy et al (2018) who found the mean values of S. aureus in examined kofta, luncheon, burger, and shawerma samples were 2.04x10 3 , 7.2x10 3 , 1.9x10 3 , and 8.3x10 3 CFU/g, respectively. The variation in the results between different authors may be due to the differences in hygienic measures during manufacturing practices, handling, and the effectiveness of thermal treatment applied during preparation.…”
Section: Discussionmentioning
confidence: 82%